Decomposition of socioeconomic inequality in COVID‐19 mortality in Iran: A retrospective cohort study. (5th November 2021) - Nemati, Saeed; Saeedi, Elnaz; Abdi, Sepideh; Qandian, Ali; Kalhor, Esmaeil; Moradi, Samin; Joshang, Narges; Eftekharzadeh, Anita; Hatamzadeh Khanghahi, Masoud; Fattahi, Pedram; Vand Rajabpour, Mojtaba; Najari, Hamid Reza
Abstract: This study aimed to investigate the relationship between socioeconomic status and COVID‐19 mortality in Iran. We performed a retrospective cohort study on data from the hospitalised COVID‐19 patients in Qazvin. We collected data on education, self‐reported socioeconomic status, and location of residence as a proxy for socioeconomic status (SES). We applied the Blinder‐Oaxaca decomposition approach to assess the role of socioeconomic inequality in COVID‐19 mortality and determine the main contributors to the observed inequality. Overall, 941 patients (48.96%) had low SES, while only 24.87% ( n = 478) were classified in the high SES category. The mortality rate was significantly higher in the low SES group, and we spotted a 17.13% gap in COVID‐19 mortality between the high and low SES patients ( p < 0.001). Age was the main contributor to the observed inequality, responsible for 6.91% of the gap ( p < 0.001). Having co‐morbidities (1.53%) and longer length of stay (LOS) in hospitals (0.95%) in the low SES group were other main determinants of the inequality in COVID‐19 mortality ( p < 0.05). In the unexplained part of our model, the effect of increased age (10.61%) and a positive RT‐PCR test result (3.43%) were more substantial in the low SES group compared to the high SES patients ( p < 0.05). The low SES people had an increased risk of getting COVID‐19, and the disease has been more severe and fatal among them. Increased age, co‐morbidities, and LOS were identified as the main drivers of this inequality.